HUKUM ADAT DI INDONESIA PERSPEKTIF SOSIOLOGI DAN ANTROPOLOGI HUKUM ISLAM - Sumanto, Dedi (IAIN Batusangkar, 2018)
This paper aims to reveal the implementation of customary law in terms of the form of marriage carried out in several regions in the portrait of the sociology and anthropology of Islamic law. The study was carried out with a socio-cultural approach through phenomena in the field that were in accordance with the literature and empirical observations of each customary event related. The method used is Library Research and observing phenomena in the field regarding customary law that applied in the community. The results of the study in customary law shown that based on reality, social and cultural customary law communities in Indonesia indicated the form of marriage as an Honest Marriage, Semenda Marriage, Free Marriage, Mixed Marriage and Out of Law Marriage as the forms of legal cultural habits that exist in a customary community in the form of unwritten so that the functions and applications can be carried out in accordance with the obedience of the law based on a sense of justice in society and practice in the community where the written law is not always in line with developments in society. It can be conluded that the written rules cannot solve existing problems and sometimes it does not reflect a sense of justice in society.